2020
DOI: 10.3390/ijerph17197014
|View full text |Cite
|
Sign up to set email alerts
|

Is a View of Green Spaces from Home Associated with a Lower Risk of Anxiety and Depression?

Abstract: Although a large body of research supports the theory that exposure to nature results in mental health benefits, research evidence on the effects of having a view of green space from home is still scarce. The aim of the present study is to assess the impact that access to a green space view from home has on anxiety and depression. This is a cross-sectional study extracting data from the “2018 Green Spaces, Daily Habits and Urban Health Survey” conducted in Carmona (Spain). The study included variables on socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 36 publications
3
37
1
2
Order By: Relevance
“…The current study identified indirect adverse pathways from the visibility of nature through windows to mental health problems represented by depression and anxiety symptoms. The results support a previous study where the views of greenspaces from home were associated with a lower risk of anxiety and depression ( 22 ). A later study has also confirmed the same benefits for isolated people during the COVID-19 pandemic ( 21 ), which underlines the values of nature exposure for the isolated population.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current study identified indirect adverse pathways from the visibility of nature through windows to mental health problems represented by depression and anxiety symptoms. The results support a previous study where the views of greenspaces from home were associated with a lower risk of anxiety and depression ( 22 ). A later study has also confirmed the same benefits for isolated people during the COVID-19 pandemic ( 21 ), which underlines the values of nature exposure for the isolated population.…”
Section: Discussionsupporting
confidence: 91%
“…Windows can contribute to indirect nature exposure ( 22 , 23 ). According to previous studies, the visibility of nature is a fundamental dimension for nature exposure through windows ( 21 , 22 ), which may be affected by neighborhood greening rate and the geographical location of windows.…”
Section: Conceptual Framework Of Exposure-response Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, housing design and environmental conditions may sustain the viability of health and delivery around certain survivorship care domains through psychosocially supportive spaces that promote recovery. In the context of health effects associated to influencing factors in home settings, pre-COVID-19 systematic and primary research has also shown how the contact with domestic indoor nature [200], view of green spaces [201,202], natural and artificial lighting [203], environment sounds [204], household air pollution [205,206], thermal comfort and building features and ventilation/heating systems following housing improvements [207,208] can impact on residents' health and mental well-being. Of these primary studies, the majority used non-objective measurements for evaluating the different home environmental domains and health-wellbeing outcomes.…”
Section: Housing As An Essential Component For Sustainable Primary Care and Public Health Integrationmentioning
confidence: 99%